Farmers’ Perceptions of Climate Change. A Case of Nakasongola District in Uganda (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Background: Ugandan farmers are susceptible to the changing climate with unpredictable rainfall distribution and severe rising temperatures. Climatic change is likely to affect the basic elements of life for people around the world resulting into no access to water and food production, hence hundred millions of people could suffer hunger and water shortages leading to severe death. This paper is aimed at exploring farmers’ perceptions of climate change.Material and method: The study employed a case study design where several instrumental bound cases are examined. We utilized multiple data collection methods to explore perceptions of climate change. We also chose the qualitative-focused enquiry for this study because this approach allows the comparison of different stakeholders’ perspectives drawn primarily from a qualitative approach. Data were collected using semi-structured interviews from fifteen purposefully selected local farmers from selected sub counties.Results: Findings revealed that farmers perceive climate change news as a source of negative excitements such as fear, worry and intimidation. Similarly, findings revealed that bush burning, deforestation, bush burning and over grazing are the major causes of climate change. In addition to ignorance amongst the people who are not clearly aware of what climate change is and they don’t know why they receive little rain fall, why very hot days.Conclusion: This research study revealed a number of key ideas and it is concluded that some people are not informed clearly of what is causing climate change and the inadequate information about climate change needed to be improved to help the entire generation understand climate change. And it was thus concluded that people’s awareness on climate change is vital for a sustainable livelihood.